MINAT WIRAUSAHA KAUM SANTRI DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA (STUDI PADA PONDOK PESANTREN AR-RIYADH PALEMBANG) - Nadhira Ulfa, Nadhira Ulfa Nadhira Ulfa (I-Economics, 2015)
The aims of this research are to explore and analyze the factors that was effected the entrepreneurship intention of the senior students of islamic boarding school Ar-Riyadh Palembang. Nowdays the senior students of islamic boarding school of Ar-Riyadh and his alumni has begun to abondan the intention of entrepreneurship  as it leads to developing his social economics matters. Using quantitative procedures, this research finds out that parsially t test shows t-valued 7,171 > than t-table 1,665. And simultaneously f test shows f-valued 88,136 > than v-table 3,97. From above findings, this reseach could explined that the entrepreneurship intentions of senior students of Ar-Riyadh Palembang has high category it had been reach  96,2 %. Internal and exsternal factors was significanlty effected his entrepreneurship intentions. Key Words:Entrepreneurship, Intentions, Senior Students, and Islamic Boarding School